My body moves in music therapy : body movements and their role in music therapy in the treatment of depression and an eating disorder : a case study - Karvonen, Riikka (2015)
Music and dance play an important role in every culture and society. In some parts of the world, the word for music and dance is the same. Due to this, one good treatment and psychological support can be music and dance. The purpose of this master’s thesis was to investigate how body movements and their role in music therapy in the treatment of depression and an eating disorder can offer one insights, and improve depression and quality of life. This case study was conducted within a clinical setting. The client attended 12 music therapy sessions that were recorded with video and audio. The recordings were beneficial for the data analysis to be used in my thesis, which took the form of deductive qualitative content analysis. The findings were reported by analyzing quotations from the data using direct data citations and the researcher’s own insights and interpretation. The results of this study show that the client’s self-esteem was strengthened by the use of music, and the client’s own body movement and dance. Music supported the movement and dance. The body-centered approach and music interventions helped to expand the client’s experiences. They reinforced her mental well-being and supported self-esteem and self-expression.